Ultrasound color pattern of colonic hamartomatous polyps - Chih-Hsuan Chen; Yang-Yuan Chen; Hsu-Heng Yen (Journal of Medical Ultrasound, 2023)
Colonic hamartomatous polyps are clinically benign tumors. Colonic hamartomas are polypoid lesions that are rare in adults and most commonly encountered in infants and children. We report an unusual case of giant colonic hamartomatous polyps that were found incidentally during a medical workup for acute lower gastrointestinal bleeding in a 26-year-old woman. We present the color Doppler ultrasound, computed tomography scan, and endoscopic pattern of colonic hamartomatous polyps.